Defamiliarisasi dalam Kebahasaan Cerpen Jumat,Yang Sebening Gelas Anggur Karya Hasta Indriyana - Uniawati Uniawati (KAJIAN SASTRA, 2008)
The concept of defamiliarisation represents the concept which is brought about by formalism. The concept is emphasized by the application of close reading, taking the texts the only consideration in analyzing it. The focus is to undo the easiness of understanding a text with a purpose to make the text more interesting. The text studied here is